Synthesis of some biologically active monoazo disperse dyes derived from nicotinic acid derivatives under microwave irradiation for dyeing polyester fabrics - El-Apasery, Morsy Ahmed; Al-Qalaf, Fawzia; Almohammad, Khaledah; Mahmoud, Huda (European Journal of Chemistry, 2013)
2-Amino- and 2-hydroxy-6-substituted-5-arylazonicotinates monoazo disperse dyes 6 and 7a,b were prepared via condensation of 3-oxo-3-substituted-2-arylhydrazonals 2a-c with ethyl cyanoacetate using microwave irradiation as an energy source. Fastness properties of the dyed samples were measured. All of the dyed fabrics tested, displayed excellent washing and perspiration fastness and moderate light fastness. Finally, the biological activities of the synthesized disperse dyes against Gram-positive and Gram-negative bacteria, and yeast were evaluated.